PEMBENTUKAN PREKURSOR FLAVOR PADA BIJI KAKAO MELALUI HIDROLISIS ENZIMATIS ENDOGENOUS TERKENDALI YANG DIUKUR BERDASARKAN INDEKS GULA - , DEWI PRASTIKA, Dr. Ir. Supriyanto, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of cocoa beans processing steps which affect the end quality is flavor precursor formation through enzymatic hydrolysis. Flavor precursor formation using a controlled endogenous enzymatic hydrolysis might be useful because all of parameters which influence cocoa beans quality can be controlled. The aim of this study is to choose the incubation conditions that can produce 100 % sugar index and compare the quality of cocoa beans at selected conditions with the conventional fermented cocoa beans by farmers based on sugar index, color index, and organoleptic tests. Main material of this research was ripe cocoa pods from PT. Pagilaran farm in Samigaluh, Kulon Progo district. Research parameters were temperature with two levels i.e.: 45oC and 55oC, variations in the incubation medium acidity at pH 3,5